Locutionary act in motivating students at SMPN 2 Wungu - Bella Agustina Santoz; Nuri Ati Ningsih; Agita Risma Nurhikmawati (Universitas PGRI Madiun, 2018)
The aim of this research is to explain the speech act which is used to motivate students at SMPN 2 Wungu. The objective of this research is to explain the type of locutionary act which is used to motivate students. The research approach is qualitative method using observation and interview to collect the data. In this research, the researcher takes three teachers for source of data. Data and method triangulation are used to perform the data validity. Data are analyzed under interactive model. The result of this analysis are there are 26 (52%) utterances that belong to indirect speech act and 24 (48%) utterances belong to direct speech act, thus, it can be concluded that the type which is used to motivate students at SMPN 2 Wungu is indirect speech act.